Microplastics in Florida, United States: A Case Study of Quantification and Characterization With Intertidal Snails - Kleinschmidt, Jordan M.; Janosik, Alexis M. (Frontiers in Ecology and Evolution, 2021)
Concentrations of microplastics are increasing within the oceans, including waters surrounding Florida, United States. Miles of sandy beaches make the sunshine state a prime tourist destination leading to an increased amount of pollution along Florida coasts. Microplastics can cause damage to intertidal organisms, as well as causing issues up the food chain with biomagnification and seafood consumers, such as humans. Florida is also subject to hurricanes which often distribute sediments, filling the water column with previously settled microplastics. These factors make Florida a special case to review considering the state is affected heavily by hurricanes and tourism, which can contribute to microplastic concentrations in the Gulf of Mexico. The focus of this study was to quantify, characterize, and compare microplastics contamination in two predatory marine snail species from intertidal habitats in Florida, United States Ingestion results were also compared to microplastics contamination of water samples collected from the same locations. Red-mouth rock shell (Stramonita haemastoma, n = 30) and Crown conch (Melongena corona, n = 30) snails were collected from intertidal habitats in Florida and digested for microplastics quantification. Water samples were filtered and microplastics were quantified. 256 microplastics, of which 93% were microfibers and 7% were microfragments were isolated from snails (n = 60). Additionally, 67 microplastics were isolated from 8 L of seawater (8.375 microplastics/L), of which 97% were microfibers and 3% were microfragments. This is the first known study to demonstrate microplastics contamination of tissues in predatory marine intertidal snails. Marine intertidal snails may be good organisms for biomonitoring of microplastics in intertidal sandy habitats.